THE STRUCTURE OF THE SIBERIAN GEOGRAPHICAL FLORAL ELEMENT IN THE MIDDLE SIBERIAN FOREST STEPPES - E. M. Antipova (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. The ultimate goal of studies of any flora is the clarification of the history of vegetation cover and individual taxa formation in the studied region, determination of the degree of its individuality, of floristic links with other territories, and of regularities in flora formation.Materials and methods. The flora of vascular plants in the island forest steppes of Middle Siberia, i. e. of the Krasnoyarsk, Kansk and Achinsk forest steppes, identified by the specific floras method of A. I. Tolmachev, was chosen as the object of research. The purpose of the paper was to study the structure of the Siberian geographical element in the steppe flora, characteristics of the types of constituent distribution areas selected on the basis of the phytochorion concept. The basis for determining the types of habitats was the planetary regionalization scheme by A. L. Takhtajan, complemented by statistical convergent zonation for Siberia by L. I. Malyshev, and for the Russian Far East by R. V. Kamelin.Results. The territory of the Middle Siberian forest steppes is a part of the Altai-Yenisei Province. The Krasnoyarsk, Kansk and Achinsk forest steppes (Krasnoyarsk Territory) are the most northern parts of the region (55°28’–57°28’N, 89°– 96°40’E). Twenty-six local floras were examined. Ten distribution area types were identified within the Siberian geographical element of the boreal group according to the names of sub-regions and provinces (154 species, 11.12%), limiting their distribution from West to East or from East to West, including all intermediate Siberian provinces between them. All types of distribution areas were combined into four large subgroups, namely Siberian, West Siberian, Middle Siberian, and East Siberian. Names of geographical elements were composed from the names of several phytochoria, in which they had been registered, according to the rules by M. G. Popov.Conclusions. The Siberian geographical element rates third in all three forest steppes after the Euro-Siberian and Circumboreal geographical elements. In the flora of the Middle Siberian forest steppes Siberian elements amount to 11%, among which the Middle Siberian ones prevail (4.4%, 61 species) due to the geographical position of the flora. The fraction of species distributed throughout Siberia is 3.25% (45 species), followed by East Siberian species (2.24%, 31 species) and West Siberian ones (1.23%, 17 species).